2013
DOI: 10.5120/10001-4212
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Function by using a New MATLAB based Genetic Algorithm Procedure

Abstract: As the applications of systems are increasing in various aspects of our daily life, it enhances the complexity of systems in Software design (Program response according to environment) and hardware components (caches, branch predicting pipelines). Within the past couple of years the Test Engineers have developed a new testing procedure for testing the correctness of systems: namely the evolutionary test. The test is interpreted as a problem of optimization, and employs evolutionary computation to find the test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…MATLAB is one of the most popular environments that are used in many research areas. Therefore, Purohit et al explored the prospect of GA for optimization using Rastrigin function inside MATLAB. The authors used the optimization tool in MATLAB where they selected the option ga—Genetic algorithm as a solver and rastriginsfcn as fitness function, and the diversity of population can be detected by measuring the average distance between individuals.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…MATLAB is one of the most popular environments that are used in many research areas. Therefore, Purohit et al explored the prospect of GA for optimization using Rastrigin function inside MATLAB. The authors used the optimization tool in MATLAB where they selected the option ga—Genetic algorithm as a solver and rastriginsfcn as fitness function, and the diversity of population can be detected by measuring the average distance between individuals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…GA depends on selecting the most effective solution among wide space of solutions, so in order to execute GA, a primary population should be created, where any individual in the population is considered as a chromosome, and this algorithm is inspired from evolution's theory by Darwin “survival of fittest.” The most adequate individual in any population has the best chance to be reproduced into the next generation. GAs are based on biological basics, which are easy to construct and their implementation does not need a huge amount of storage that is why GAs are an appropriate choice for optimization problems …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For most of optimizing problems in the real world, there are constraints to be satisfied. A particular difficulty in handling constrained optimization is that the solutions cannot be guaranteed to be feasible for all results during the searching process [12,13]. Hence evolutionary algorithms like Genetic Algorithm (GA) are incapable of optimizing the constrained problem directly, and some techniques must be introduced to the optimization under constraints [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 However, in order to enable further advances of this technology, it is essential to have a known and reliable relationship between the input parameters and their desired output results, such as material removal rate and kerf taper, so that the optimum process parameters can be identified. [4][5][6][7][8][9][10][11] The quality of surfaces generated by AJM has been discussed by many investigators seeking to estimate the effects of process parameters. Balasubramaniam et al [12][13][14] found the surface generated had a reverse bell-mouthed shape, with entry side diameter in the target material depending on the values of the process parameters.…”
Section: Introductionmentioning
confidence: 99%